2009
DOI: 10.3989/scimar.2009.73n3487
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial community structure of mangrove sediments in relation to environmental variables accessed by 16S rRNA gene-denaturing gradient gel electrophoresis fingerprinting

Abstract: suMMaRY: Bacterial community structure and the relationship between environmental variables and microbial communities in the surface sediments of tropical mangrove ecosystems were investigated in sanya, hainan island, China. Profiles of bacterial communities were generated using culture-independent PCR-denaturing gradient gel electrophoresis (dgge), and the results were interpreted with multivariate statistical analysis. Findings suggested that microbial communities varied with sample collection sites and seas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 32 publications
(23 reference statements)
0
17
0
3
Order By: Relevance
“…), and also by the seasons (Zhang et al . ). Additionally, it is possible that the composition of the microbial community is subject to maritime influence.…”
Section: Introductionmentioning
confidence: 97%
“…), and also by the seasons (Zhang et al . ). Additionally, it is possible that the composition of the microbial community is subject to maritime influence.…”
Section: Introductionmentioning
confidence: 97%
“…The resulting range of univariate analyses such as Shannon-Wiener index (1.981 to 2.451), Simpson species richness (0.833 to 0.898), Pielou's evenness (0.833 to 0.929), Margalef species index (2.35 to 3.99), Simpson dominance (0.102 to 0.162), and Fisher-α (6.04 to 12.38) recorded the respective chosen tested mangrove sediment and root samples. From this, the Similarly, Zhang et al (2009) reported the low and high values of Shannon species index of rhizosphere sediment and root sample of tropical mangrove ecosystem located at the southernmost part of Hainan Island in China. For instance, Das et al (2006Das et al ( , 2009 reported the diversity and distribution of total heterotrophic bacterial and filamentous fungal communities in different location of the Bay of Bengal coast.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have indicated that mariculture systems, including intensive fish and shrimp farms, integrated mangrove forest aquaculture systems and cage farms, are responsible for the discharge of significant quantities of effluent into the surrounding mangrove ecosystems (Troell et al, 1999;Fitzgerald, 2002;Wei et al, 2009;De Silva, 2012), due to the fact that nutrient enrichment and the presence of residual waste from the effluent alter bacterial communities (Zhang et al, 2009;Ghosh et al, 2010). However, fewer researchers investigated the bacterial community of seawater in mangroves affected by the mariculture.…”
Section: Discussionmentioning
confidence: 98%